Solve for x 4(x+3)=36

Math
4(x+3)=36
Divide each term by 4 and simplify.
Tap for more steps…
Divide each term in 4(x+3)=36 by 4.
4(x+3)4=364
Cancel the common factor of 4.
Tap for more steps…
Cancel the common factor.
4(x+3)4=364
Divide x+3 by 1.
x+3=364
x+3=364
Divide 36 by 4.
x+3=9
x+3=9
Move all terms not containing x to the right side of the equation.
Tap for more steps…
Subtract 3 from both sides of the equation.
x=9-3
Subtract 3 from 9.
x=6
x=6
Solve for x 4(x+3)=36

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top